Assistive Technology and Cognitive-Behavioral Programs for Promoting Adaptive Skills of Persons with Alzheimer Disease: A Selective Review - Perilli, Viviana; Stasolla, Fabrizio; Maselli, Stefania; Morelli, Isabel (Journal of Neurological Research And Therapy, 2018)
Background: Person with Alzheimer Disease may present cognitive, social, communication, physical, and orientation impairments. Furthermore, individuals with Alzheimer Disease may exhibit challenging behavior, isolation, and passivity. Objectives: To emphasize the role of Assistive Technology-based interventions and Cognitive-Behavioral Programs to improve the independence, and the quality of life of patients with Alzheimer Disease. To assess the effects on teaching adaptive responding, and decreasing challenging behaviors. Method: A selective literature review was carried out considering Alzheimer, Assistive Technology, Cognitive-Behavioral Programs, Adaptive Responding, Challenging Behaviors, and Quality of life as keywords. Twenty-six studies were reviewed. Results: Empirical data demonstrated the effectiveness, and the suitability of the selected interventions, although few failures occurred. The participants involved significantly increased their adaptive responding during the intervention phases, and maintained their performance over the time. Conclusion: Assistive Technology-based rehabilitative programs and Cognitive-Behavioral Interventions may be helpful for promoting the independence and the quality of life of individuals with Alzheimer Disease.
Keywords: Alzheimer Disease; Assistive Technology; Cognitive-Behavioral Programs Independence; Quality of Life; Adaptive Skills.